Metal–organic framework derived hollow porous CuO–CuCo2O4 dodecahedrons as a cathode catalyst for Li–O2 batteries. Issue 29 (24th May 2019) - Zhen, Shu-ying; Wu, Hai-tao; Wang, Yan; Li, Na; Chen, Hao-sen; Song, Wei-li; Wang, Zhen-hua; Sun, Wang; Sun, Ke-ning
Abstract : Metal–organic framework derived porous CuO–CuCo2 O4 dodecahedrons as a cathode catalyst for Li–O2 batteries with significantly enhanced rate and cyclic performance. Abstract : Herein, hollow porous CuO–CuCo2 O4 dodecahedrons are synthesized by using a simple self-sacrificial metal–organic framework (MOF) template, which resulted in dodecahedron morphology with hierarchically porous architecture. When evaluated as a cathodic electrocatalyst in lithium–oxygen batteries, the CuO–CuCo2 O4 composite exhibits a significantly enhanced electrochemical performance, delivering an initial capacity of 6844 mA h g −1 with a remarkably decreased discharge/charge overpotential to 1.15 V ( vs. Li/Li + ) at a current density of 100 mA g −1 and showing excellent cyclic stability up to 111 charge/discharge cycles under a cut-off capacity of 1000 mA h g −1 at 400 mA g −1 . The outstanding electrochemical performance of CuO–CuCo2 O4 composite can be owing to the intrinsic catalytic activity, unique porous structure and the presence of substantial electrocatalytic sites. The ex situ XRD and SEM are also carried out to reveal the charge/discharge behavior and demonstrate the excellent reversibility of the CuO–CuCo2 O4 based electrode.